Transnational Voices in Academia: Narratives of Identity and Positionality through Research and Teaching - Norova, Nasiba; Gutiérrez, Juan David (Journal of International Students, 2024)
In this paper, two transnational doctoral students and language educators of color engage in a reflexive dialogic conversation focusing on intersectional aspects of their identities and positionalities. Utilizing duoethnography research methodology, they explored their academic and professional journeys in post-secondary education both in their home countries and in an Anglophone context. A discussion on the negotiation of their positionalities in their immediate academic, professional, and sociocultural contexts is provided. We argue that unveiling one’s positionality requires a prolonged reflexive engagement that assists in establishing quality in qualitative research as well as exploring fluidity in positionality. We close with implications and invitations to use duoethnography as a path to self-exploration, solidarity, and allyship.